Pesticide Residues, Glyphosate Adsorption and Degradation Characteristics in Ethiopian Agricultural Soils - Bereket Ayenew; Endalkachew Getu (Environmental Health Insights)
Background: The decline in wheat output in Ethiopia is widely attributed to pests, which has led to a rise in the usage of pesticides to boost productivity. The degree of pesticides sorption and degradation which influence the likelihood of environmental contamination from pesticides seeping into water bodies from soil has not yet been published for Ethiopian soils. The study aimed at to quantify the levels of pesticide residues, assess glyphosate’s adsorption capabilities and degradation rate in the soils. Materials and methods: QuEChERS method of extraction was employed to determine the concentration of the respective pesticides. The adsorption capacities of glyphosate in agricultural soils of Cheha and Dinsho districts were measured using batch adsorption techniques. Results: Six pesticide residues were found in 12 soil samples at varied quantities. Glyphosate (24.00-219.31 µg kg −1 ), s-metolachlor (23.67-220.67 µg kg −1 ), chlorpyrifos (27.74 202.67 µg kg −1 ), pyroxulam (14.67-50.65 µg kg −1 ), florasulam (78.00-250.67 µg kg −1 ), malathion (15.00-49.67 µg kg −1 ). The experimental results showed that glyphosate was slightly sorbed at SD10 soil (18.91 μg −1−n mL n g −1 ) in comparison to SC1 soil (114.66 μg −1−n mL n g −1 ). Organic matter and clay content proving to be the principal factors influencing the process. According to adsorption experimental data, chemisorption is the major process in glyphosate adsorption, with the pseudo-second order kinetic model providing the best fit ( R 2  = .99). The soils in the study area exhibit notable variations in glyphosate rate of degradation (0.0076-0.0221 week −1 ). The findings show that the main soil variables affecting the half-life (glyphosate degradation) were clay concentrations ( R 2  = .48; P  = .013), pH ( R 2  = .55; P  = .0055), Organic matter ( R 2  = .74; P  = .00027), Fe ox ( R 2  = .50; P  = .0105), and Al ox ( R 2  = .73; P  = .00046). Conclusion: The weak glyphosate adsorption capabilities of soils can be a good indicator that the pesticide residues in the soil are poised to endanger soil organisms and contaminate nearby water bodies through runoff and leaching.